Pre-breeding evaluation of rice genotypes for biofortification in Telangana region - Dubbala, PDV; Narkhede, GW; Thota, S; Akshitha, NY; Sharanabasav, H; Subhashree, D (Plant Science Today, 2026)
In India, rice (Oryza sativa L.) is the primary staple food consumed by a significant percentage of its population, but the polished grain of rice is low in essential micronutrients, including iron (Fe) and zinc (Zn), which contributes to micronutrient malnutrition in a huge percentage of the Indian population. The aim of the current research was to assess genetic variation, agronomic performance, grain quality traits and micronutrient content of famous rice genotypes grown in Telangana and Andhra Pradesh regions with the aim of finding an appropriate donor to practice genetic biofortification. Evaluation of 16 rice genotypes was done at the kharif season in 2024 under irrigated conditions and with a randomized block design in 3 replications. The analysis of variance, the parameters of genetic variability, correlation and path coefficient analysis and principal component analysis (PCA) were used to analyze 18 agronomic, quality and nutritional traits. The genetic variation of most traits was found to be highly significant (p<0.01). Both grain iron and zinc levels showed a moderate level of genotypic coefficient of variation (12.50 % and 14.05 %, respectively) with high heritability and genetic progression, which mean that it is highly genetically controlled. Iron and zinc contents had a strong positive relationship (r = 0.65), which implied that it would be feasible to improve simultaneously. Principal component analysis indicated that the four major components could account 82.2 % of the overall variation and the loading of iron and zinc was also high in the second major component. KNM 118 and Bhadrakali had the best iron (15.8 and 14.5 mg kg-1) and zinc (28.3 and 27.0 mg kg-1), whereas KNM 1638 and Varalu had better grain yield and productivity. The findings show that there is a genetic variability that can be exploited to biofortify rice with micronutrients in popular rice genotypes and indicate potential donor lines to generate high yield, iron and zinc-enriched rice varieties. These genotypes can also be used in targeted breeding programmes and confirmed by multi-location trials that can be used to enhance nutritional sustainability.